IMPLEMENTASI KURIKULUM 2013 MELALUI PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SEKOLAH MENENGAH PERTAMA (SMP) - Saubas, H.Udin (Universitas Khairun, 2015)
Learning by using scientific approach is a process of learning that is designed that make the students construct a concept actively, role or princip trough observation step (to identify or to find a problem), stated a problem, propose hypothesis, collecting data by using variety technic, analyze data, getting conclusion, and communicate the concept that find. Therefore, in the learning process that hoped to stimulate the students in searching the source by an observation, not only know by the teacher.The scientific approach role in learning process by skill process like observation, classification, assessment, explain, and making conclusion. In doing that process, the students need a helping from teacher. But the helping must less because the students’ class is in high level. Key word: Implementation of 2013 curriculum, scientific approach Implementation, Indonesia language learning text base